2010
DOI: 10.1073/pnas.1000175107
|View full text |Cite
|
Sign up to set email alerts
|

Distinct frontal systems for response inhibition, attentional capture, and error processing

Abstract: Stopping an action in response to an unexpected event requires both that the event is attended to, and that the action is inhibited. Previous neuroimaging investigations of stopping have failed to adequately separate these cognitive elements. Here we used a version of the widely used Stop Signal Task that controls for the attentional capture of stop signals. This allowed us to fractionate the contributions of frontal regions, including the right inferior frontal gyrus and medial frontal cortex, to attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
470
8
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(523 citation statements)
references
References 37 publications
43
470
8
2
Order By: Relevance
“…17,18 These results are in agreement with previous studies investigating the implicit regulation of food choice and craving for cigarettes. For example, Hare et al 8 found increased responses in the left DLPFC when dieters with high self-control (compared with dieters with low self-control; as assessed by choice of healthy or unhealthy food) chose healthy over unhealthy food in an implicit regulation experiment.…”
Section: Discussionsupporting
confidence: 83%
“…17,18 These results are in agreement with previous studies investigating the implicit regulation of food choice and craving for cigarettes. For example, Hare et al 8 found increased responses in the left DLPFC when dieters with high self-control (compared with dieters with low self-control; as assessed by choice of healthy or unhealthy food) chose healthy over unhealthy food in an implicit regulation experiment.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, although several data [e.g. (Sharp, et al, 2010;Velanova, et al, 2008)] suggested the involvement of the cingulate cortex in cognitive processes associated with erroneous performance, it seems unlikely that the association we observed here between Val load allele effect and cingulate activity came from error-related activity, because only correct responses were used in the fMRI analyses. However, the number of errors committed by the participants in the different contexts was very low (from 2 to 10 %), precluding the exploration of this issue in a statistically meaningful way.…”
Section: The Role Of Dopamine In the Implementation Of Proactive Cognmentioning
confidence: 68%
“…The left IFG has shown causal relevance to stopping behaviours in patients with lesions [46] and also increased BOLD activity in healthy participants during action restraint on a go-nogo task [47] or tasks requiring inhibitory control for interference resolution [48]. Some imaging evidence with the stop signal task has considered the right IFG as a key node in the inhibitory network [49]; whereas other imaging studies attributed a role in attention rather than inhibition to the IFG [50]. Thus, a contribution from the left IFG may partly explain our negative results after cTBS over the right IFG.…”
Section: Motor Inhibitionmentioning
confidence: 99%